2021
DOI: 10.47678/cjhe.vi0.188971
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Canadian Distance Educators on the Move to Online Learning

Abstract: Our qualitative study explored transition in seven Canadian universities—early providers of distance education that transitioned to online learning between 2002 and 2017. We interviewed 16 individuals who were involved in the design, planning, or implementation of online learning. Participants reported their universities experienced significant impacts on organizational structure and roles. Many saw an increased focus on learning and teaching. Access, revenue generation, and technology were identified as drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…To support the current situation, lecturers as instructional designers must be professional and have the awareness to improve technological capabilities that are integrated in teaching and learning. This is very much needed for the maximum implementation of online learning [34]. Several relevant findings support the findings of this study that lecturer performance greatly contributes to increasing student satisfaction in learning activities.…”
Section: Figure 3 the Results Of Testing The Measurement Model And St...supporting
confidence: 86%
“…To support the current situation, lecturers as instructional designers must be professional and have the awareness to improve technological capabilities that are integrated in teaching and learning. This is very much needed for the maximum implementation of online learning [34]. Several relevant findings support the findings of this study that lecturer performance greatly contributes to increasing student satisfaction in learning activities.…”
Section: Figure 3 the Results Of Testing The Measurement Model And St...supporting
confidence: 86%
“…Numerous studies in the literature have reported the challenges that students and instructors in some countries faced in DL. In Canada, Ives & Walsh (2021) explored the transition to DL in seven universities between 2002 and 2017 and found that the challenges that faced those universities included resistance to change from traditional face-to-face learning and teaching to online learning, lack of effective, visionary leadership and lack of dedicated resources.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the virtual learning environment in which teachers deliver courses would enable them to contribute significantly toward improved e-learning course design. According to Ives and Wash (2021), teachers state that increased emphasis on designing courses for effective learning leads to improving the overall quality of classroom instruction. Moreover, after completing specialized training courses and upon gaining greater e-learning skills, the appreciation for teachers' competence and impact on specialist education design, development methodologies and online pedagogies increases in the eyes of HEI management (Kirkova-Bogdanova, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Avenues for future research According to Gupta et al (2020), while HEIs have understood the significance of success factors such as expected teachers' competence, this has not been fully aligned with students' and industry expectations from academia, and further research into the topic can help bridge the gap and bring about a more complete digital transformation for HEIs by ensuring success factors for effectiveness are met. Future studies that explore the perspectives of teachers could ensure their needs are considered as education progressively becomes more onlinebased, and consequently, there is a need for further exploratory research on HEIs leadership initiatives, management actions and processes required to support these disruptive academic changes in the HE industry (Ives and Walsh, 2021). Seeing as the teacher's perspective on elearning effectiveness success factors is underrepresented in extant literature (Kumar et al, 2019), further research is desirable on the different forms of support that are necessary to facilitate the abrupt transition where teachers find themselves having to emergently engage in e-learning teaching in the aftermath of the COVID-19 pandemic (Pedro and Kumar, 2020).…”
Section: Discussionmentioning
confidence: 99%